THE PROBLEM OF THE DEVELOPMENT OF PERCEPTION AND IMAGINATION OF WORKS OF FINE ART IN SCHOOLCHILDREN AND THE STATE OF ITS STUDY BY FOREIGN SCIENTISTS - Остонова Гулшод Раззоқовна (Web of Journals Publishing, 2025)
This article provides brief information on the problem of the development of perception and imagination of works of fine art in schoolchildren and the state of its study by foreign scholars.
Keywords: Fine arts, pedagogy, psychology, method, perception, imagination, student, teacher.